Comparison Analysis Of Consumer Purchasing Decisions On Conventional And Syariah Mini Markets (Case Study on Alfamart and 212 Mart in Medan City) - Nasution, Asrizal Efendy; Putri, Linzzy Pratami (AIBPM Publisher, 2019)
Today's modern markets are mostly conventional-based modern markets. With the change of life values in a more religious direction, consumers began to look for a modern syariah-based market. 212 Mart present as an answer to meet the demands of consumers who want to shop in the modern syariah-based market. But its new presence, not yet able to compete and seize the existing market. For that, it needs to be researched what factors exist in the conventional modern market thus making it able to grow and thrive as it is today. By knowing these factors, 212 Mart can follow and develop these factors based on syariah. There are many factors that can influence the decision of consumer purchase including price, promotion, service, trust and consumer’s characteristic. The purpose of this research is to know and analyze the influence of the price, promotion, service, trust and consumer’s characteristic of consumer buying decisions and analyze the difference in the buying decision. In this study using a comparative associative approach with the research object was the customer Alfamart and 212 Mart Medan. Testing was conducted by double linear regression tests by first conducting a classical assumption test, then a partial (t-test) and simultaneous hypothesis test was conducted (f-test). After that, look for the coefficient of determination to see how large the percentage of free variable variances affect the bound variables, then conducted independent sample t-test to see the difference of consumer buying decisions on Alfamart and 212 Mart Medan. The results of the study stated that partially conducted at Alfamart, variable price and promotion were positively and significantly influential on consumer purchasing decisions, while service, trust and consumer’s characteristic variables were not Influence positive and insignificant. While the trust and consumer’s characteristic variables at 212 Mart Medan have a positive and significant influence on consumer purchasing decisions, while price, promotion and service variables have no positive and insignificant effect. Simultaneously both at Alfamart and 212 Mart have a positive and significant influence on consumer purchasing decisions with the value of coefficient of determination respectively 26.9% and 17.4%. For the difference of consumer buying decisions on Alfamart and 212 Mart, the variable of price, promotion, trust and consumer’s characteristic have significant differences while service variable do not have significant differences.